Multiscale dynamics of a heterotypic cancer cell population within a fibrous extracellular matrix. (7th February 2020) - Shuttleworth, Robyn; Trucu, Dumitru
Highlights: In this paper we extend the model developed in (Shuttleworth and Trucu, 2019) to investigate the invasiveness of a heterotypic tumour in a multi-phase fibrous tissue environment. This examines the invasive abilities of a malignant tumour with two cancer cell sub-populations under the presence of a two-component extracellular matrix (ECM), consisting of both an oriented ECM fibre phase distribution (such as collagen and fibronectin), and an ECM non-fibre (soluble) phase, that accounts for all other ECM non-fibrous components (such as Ca2+ ions, laminin, and other soluble matrix constituents). To that end, in the context of multiscale moving boundary approach introduced in Trucu et al. (2013) (capturing the key influence of the underlying tumour invasive edge two-scale matrix-degrading enzymes (MDEs) proteolytic activity), we consider here the dynamics of the two cancer cell sub-populations progressing within the surrounding fibrous ECM and explore its multiscale evolution and interaction with the ECM fibre phase in the presence of both homogeneous and heterogeneous non-fibre ECM soluble phases. This eventually leads to the development of a novel two-part multiscale model, which comprises two interconnected multiscale systems that share the same macro-scale whilst having their own distinct micro-scale dynamics, which connect to the cancer macro-dynamics through two distinct feedback loops. Specifically, the first multiscale system controls the dynamic redistribution of micro-fibres, caused by an appropriately weighted interaction of the cancer cell and macroscopic fibre distributions and triggered via the combined spatial flux of the two cancer cell sub-populations. This results in a dynamics change of macro-scale fibres orientation and magnitude which alters continuously the macro-scale tumour dynamics. The second multiscale system explores the interfacial dynamics at the leading edge of the tumour generated by the MDEs (secreted by the spatial distribution of cancer cells from the outer proliferating rim) who exercise a cross-interface molecular transport that degrades the peritumoural ECM, triggering this way significant changes in the tumour boundary morphology. Abstract: Local cancer cell invasion is a complex process involving many cellular and tissue interactions and is an important prerequisite for metastatic spread, the main cause of cancer related deaths. As a tumour increases in malignancy, the cancer cells adopt the ability to mutate into secondary cell subpopulations giving rise to a heterogeneous tumour. This new cell subpopulation often carries higher invasive abilities and permits a quicker spread of the tumour. Building upon the recent multiscale modelling framework for cancer invasion within a fibrous ECM introduced in Shuttleworth and Trucu, (2019), in this paper we consider the process of local invasion by a heterotypic tumour consisting of two cancer cell populations mixed with a two-phase ECM. To that end, we address the double feedback link between the tissue-scale cancer dynamics and the cell-scale molecular processes through the development of a two-part modelling framework that crucially incorporates the multiscale dynamic redistribution of oriented fibres occurring within a two-phase extra-cellular matrix and combines this with the multiscale leading edge dynamics exploring key matrix-degrading enzymes molecular processes along the tumour interface that drive the movement of the cancer boundary. The modelling framework will be accompanied by computational results that explore the effects of the underlying fibre network on the overall pattern of cancer invasion.